Sumoylation of the astroglial glutamate transporter EAAT2 governs its intracellular compartmentalization. Issue 8 (18th June 2014) - Foran, E.; Rosenblum, L.; Bogush, A.; Pasinelli, P.; Trotti, D.
Abstract : EAAT2 is a predominantly astroglial glutamate transporter responsible for the majority of synaptic glutamate clearance in the mammalian central nervous system (CNS). Its dysfunction has been linked with many neurological disorders, including amyotrophic lateral sclerosis (ALS). Decreases in EAAT2 expression and function have been implicated in causing motor neuron excitotoxic death in ALS. Nevertheless, increasing EAAT2 expression does not significantly improve ALS phenotype in mouse models or in clinical trials. In the SOD1‐G93A mouse model of inherited ALS, the cytosolic carboxy‐terminal domain is cleaved from EAAT2, conjugated to SUMO1, and accumulated in astrocytes where it triggers astrocyte‐mediated neurotoxic effects as disease progresses. However, it is not known whether this fragment is sumoylated after cleavage or if full‐length EAAT2 is already sumoylated prior to cleavage as part of physiological regulation. In this study, we show that a fraction of full‐length EAAT2 is constitutively sumoylated in primary cultures of astrocytes in vitro and in the CNS in vivo . Furthermore, the extent of sumoylation of EAAT2 does not change during the course of ALS in the SOD1‐G93A mouse and is not affected by the expression of ALS‐causative mutant SOD1 proteins in astrocytes in vitro, indicating that EAAT2 sumoylation is not driven by pathogenic mechanisms. Most interestingly, sumoylated EAAT2 localizes to intracellular compartments, whereas non‐sumoylated EAAT2 resides on the plasma membrane. In agreement, promoting desumoylation in primary astrocytes causes increased EAAT2‐mediated glutamate uptake. These findings could have implications for optimizing therapeutic approaches aimed at increasing EAAT2 activity in the dysfunctional or diseased CNS. GLIA 2014;62:1241–1253 Main Points: EAAT2 is constitutively sumoylated in astrocytes. Sumoylation governs EAAT2 compartmentalization favoring intracellular vs. plasma membrane localization. Sumoylation of EAAT2 is a regulatory checkpoint, which impacts the overall EAAT2‐mediated glutamate uptake in vitro and in vivo .